ЮҚОРИ СИНФ ЎҚУВЧИЛАРИ БИЛАН “ЖАҲОЛАТГА ҚАРШИ – МАЪРИФАТ” БОРАСИДАГИ ТУШУНЧАЛАР УСТИДА ИШЛАШ ТЕХНОЛОГИЯСИ - Исақулов, М.Р. (SCIENCE and SOCIETY, 2020)
The article deals with the main task put in the Conception «Youth of Uzbekiston-2030» and on their basis the author studies the issues of education of students of senior classes in the spirit of enlightenment.
Keywords: education; ignorance; to cognate the homeland; the bring up; intellectual potential; consciousness; soul; learning material; constitution; the law; interest; spirituality; right; patriotism; information culture; social activity; professionalism; physical education; creative studio